A longitudinal study on the impact of cooperative problem-based learning in inculcating sustainable development - Abdul Aziz, Azmahani (2013)
The purpose of this study was to investigate the impact of Cooperative Problem-Based Learning (CPBL) in inculcating sustainable development amongst first year engineering students. A longitudinal quantitative research methodology was carried out over three semesters to determine the changes. Students were experienced with a case study associated to sustainable issues. Precaution Adoption of Process Model (PAPM) was used as a tool to assess the students’ behaviour change which focuses on pro-self and pro-social development towards practicing sustainable lifestyles. Result showed that the implementation of CPBL as a teaching and learning approach has a positive impact on students’ development. The findings also found that elements of sustainable development should be embedded into the curriculum on the following semester to gain a continuous impact on students.